Mesopelagic particulate nitrogen dynamics in the subarctic and subtropical regions of the western North Pacific - Mino, Yoshihisa; Sukigara, Chiho; Kawakami, Hajime; Wakita, Masahide; Honda, Makio C. (Frontiers in Earth Science, 2023)
Recently, new spatiotemporal-scale particle observations by autonomous profiling floats equipped with bio-optical sensors have revealed that, in addition to gravitational particle sinking, the downward transport of surface particles by physical mixing events, which has been overlooked, contributes to particulate organic carbon export. However, the subsequent behavior of these exported particles in the mesopelagic zone (e.g., particle fragmentation and degradation) remains unclear, although it may influence the efficiency of carbon transport to further depths. This study successfully depicted new annual mean mesopelagic particulate nitrogen (PN) dynamics with multi-layer, steady-state suspended PN pools by reanalyzing seasonal data on the stable nitrogen isotopic compositions of both suspended and sinking particles, each with different profiles, from subarctic station K2 and subtropical station S1 in the North Pacific, which are both CO2 sinks but in different oceanic settings. As analytical conditions, we assumed that the net loss of sinking PN was entirely due to abiotic fragmentation of particle aggregates to non-sinking particles and that the apparent 15N enrichment associated with heterotrophic degradation in the suspended PN pools was vertically constant. The 15N mass balance for the PN supply to the uppermost mesopelagic pool, derived from such constraints, allowed us to estimate the PN export by the mixed-layer pump, which was 1.6 times greater at K2 than at S1. However, its contribution to the total export (including gravitational PN sinking) from the surface layer was approximately 20% at both stations. Moreover, the ratio of PN supplied to the uppermost pool by the mixed-layer pump and by the fragmentation of particle aggregates was also similar at both stations, approximately 1:1. Using these ratios, together with separate observations of the mixed-layer pump-driven flux, it may be possible to estimate the efficiency of POC transport due to the biological gravitational pump responsible for carbon sequestration in the deep sea.